Semiotic Exploration: Decoding the Symbolic Richness in the Nosaviraka Ngana Ri Toya Traditional Procession of the Kaili Doi Tribe - Suparni, Suparni; Mardiah, Mardiah; Agussalim, Agussalim (Yayasan Kyadiren, 2023)
The research focuses on understanding the procedural intricacies and symbolic meanings embedded in the Nosafiraka Ngana Ri Toya tradition within the Kaili Doi Tribe. The primary objective is to comprehend the ritualistic nuances of the Nosafiraka Ri Toya tradition and articulate the significance of its symbolic elements. This qualitative study adopts a descriptive approach, employing methods such as observation, interviews, and documentation for data collection. Analysis involves data reduction, presentation, and drawing conclusions for data verification. The research reveals a five-stage process in the Nosafiraka Ngana Ri Toya tradition, elucidating the meanings associated with symbols at each stage.